Radiation Effect on MHD Steady Free Convection Flow of a Gas at a Stretching Porous Surface with a Uniform Free Stream (Chemical Engineering Research Bulletin, 2013)
This article investigates the influence of radiation effect on steady free convection flow near isothermal stretching porous sheet in the presence of magnetic field. The governing equations are converted into a system of non-linear ordinary differential equations via a similarity transformation. The resulting system of nonlinear coupled ordinary differential equations are solved numerically by using the Adams-Moulton predictor-corrector method with the shooting method. The numerical results for the velocity and temperature profiles are displayed graphically showing the effect of various values of the flow parameters: radiation parameter, free convection parameter Gr, Magnetic parameter M, Prandtl number, porous parameter K and the parameter of relative difference between the temperature of the sheet, and the temperature far away from the sheet r. The effect of the radiation and magnetic field parameter on the shear stress, porosity and heat flux are discussed. FPr DOI: http://dx.doi.org/10.3329/cerb.v16i1.9287 Chemical Engineering Research Bulletin 16(2013) 16-24